Increasing the muscle contraction strength after the individualized training in football - Stoica, M.; Blejan, C. (The European Proceedings of Social & Behavioural Sciences EpSBS, 2018)
The purpose of this paper is to highlight the increase in strength of muscle contraction following the individualized training of athletes, designed after determining the maximum strength for five muscles: quadriceps, hamstrings, deltoids, pectorals and biceps brachii. Research hypothesis: The systematic use of individual programs allows increasing the maximum strength following the recruitment of a greater number of motor units. Work method: The program was applied during the competitive phase for one month, meaning that eight training sessions were held as part of further action on the aforementioned five muscle groups. It was used the flat pyramid method based on three different work intensities in order to obtain higher neuromuscular adaptation. Ten professional football players aged between 18 and 30 years participated in the designed program, working into the circuit training, therefore alternating one exercise for the upper body and one for the lower body. Conclusions: The maximum load with few repetitions leads to substantial adaptations of the nervous system, better synchronisation of the involved muscles and an increased ability to recruit fast fibers. The results of individualized strength training have increased the contraction strength by 40% after eight workouts and by more than 5% after every workout. In this regard, the research hypothesis is confirmed.